CEGAH STUNTING DENGAN EDUKASI FAKTOR-FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA - Ratna Feti Wulandari; Ratih Kusuma Wardhani; Mohammad Ikhwan Khosasih (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Lack of knowledge among mothers of children under five about stunting results in mothers of children under five being unable to assess the adequacy of nutritional needs and mothers who do not understand the use of nutrition for children's health. Providing education can increase mother's knowledge about stunting. Education affects knowledge and stunting prevention efforts. The activity was carried out at the Toddler Posyandu, Jajar Village, Wates District, Kediri Regency. The target community service activities are 20 mothers who have babies and toddlers. Activities are carried out with the stages of preparation, implementation and evaluation. Implementation time is from 16-20 December 2021. This service activity uses a questionnaire measuring instrument, the media used are leaflets and flipcharts. Most of the community service runs smoothly. The knowledge of mothers under five about stunting risk factors before being given education is mostly sufficient knowledge (65%). The education provided is an effort to change people's behavior towards a healthy life.